Scientific Views of Milorad Ekmečić According to the Origins of Načertanije: His Goals and Interpretations - Aleksić, Jovan J. (Collection of Papers of the Faculty of Philosophy in Priština, 2021)
Researching for the needs of the doctoral dissertation on the topic “Life and Work of Milorad Ekmečić (1928–2015)”, we noticed that this distinguished Yugoslavian and Serbian historian, in one period of his career, had shown special interest in search for the true creator of “Načertanije” – unofficial foreign policy program of the Principality of Serbia. Starting from the principle that in historical science nothing is explored to the end, he tackled the issue with almost axiomatic claim that Ilija Garašanin is the author of this writing. Thanks to decades of research experience, extraordinary erudition and a good command of archive material and relevant literature he managed to perform critical scrutiny. He discovered data that shed a whole new light on the background of this document. He wrote about its historical meaning and goals, but also about different interpretations of the essence of “Načertanije”, which once had a non-scientific character. He thus gave another original contribution to our historiography.